Renal protective effects of vitamin E for drug-induced kidney injury: a meta-analysis - Meng, Lingfei; Liu, Shengmao; Cui, Wenpeng (Frontiers in Pharmacology, 2025)
IntroductionAcute kidney injury (AKI) is a key clinical condition that has puzzled clinicians for many years since there is currently no efficient drug therapy. Vitamin E is found to exert a vital antioxidant role and can protect the kidney. However, clinical studies that analyze the correlation between vitamin E and AKI are scarce, and no consistent conclusions are reported from current studies. Therefore, this study was performed to evaluate the impact of vitamin E on treating AKI.MethodsThe PubMed, Embase, and Cochrane Library databases were comprehensively searched on 27 December 2023. Qualified studies were selected following the eligibility criteria. The incidence of AKI, serum creatinine, and urea nitrogen levels after vitamin E treatment were evaluated. Then, the data were combined with a fixed- or random-effects model, depending on the heterogeneity test results.ResultsSix eligible randomized controlled trials that used vitamin E for the prevention of kidney injury were included. According to our pooled analysis, vitamin E elevated eGFR levels [MD: 0.36; 95% CI (0.19, 0.53), p = 0.000], reduced serum creatinine levels [MD: −0.32; 95% CI (−0.48, 0.16), p = 0.000], and effectively inhibited the occurrence of AKI [RR: 0.69; 95% CI (0.49, 0.98), p = 0.036].ConclusionVitamin E elevates eGFR levels, reduces serum creatinine levels, and efficiently suppresses AKI occurrence.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/view/CRD42024499597, identifier CRD42024499597